Clinical Evaluation of a New, Lower Pain, One Touch Lancing Device for People With Diabetes: Virtually Pain-Free Testing and Improved Comfort Compared to Current Lancing Systems. (January 2021) - Grady, Mike; Lamps, Greg; Shemain, Ashley; Cameron, Hilary; Murray, Linda
Background: Patients worldwide use lancing devices to perform self-monitoring of blood glucose (SMBG). Continued innovation remains important to minimize pain associated with finger sticking to facilitate patient adherence to SMBG regimens. The original One Touch Delica lancer (OTD) reduced the pain of testing. This study investigated a completely re-engineered lancing system, called One Touch Delica Plus (OTDP), intended to further minimize pain while improving the patient experience. Methods: One hundred and three subjects (type 1 or 2 diabetes) experienced finger sticks with both lancing systems. Device depth and blood volume (BV) generation were determined during visit 1. These parameters were used during pain assessments in visit 2. Patient feedback was also recorded using surveys. Results: Finger-stick testing was less painful using OTDP compared to original OTD irrespective of whether 30 (−48.2 mm, −30.4 mm, P < 0.0001) or 33 gauge (−42.6 mm, 30.5 mm, P = 0.0004) lancets were used. All 103 subjects generated the required BV (≥0.4 µL) per protocol. At equivalent depth penetration, OTDP generated higher average BVs than OTD using 30 (1.58 µL, 1.10 µL) or 33 gauge lancets (1.39 µL, 0.98 µL). Subjects responded that testing with OTDP was virtually pain free (78%) and that testing with OTDP was less painful than using their current lancing systems (79%) or original OTD (67%). Conclusion: OTDP demonstrated lower pain than the original OTD lancing system and participants agreed that testing with OTDP was virtually pain free and less painful than using their current lancing systems.